2018
DOI: 10.1007/s00204-018-2256-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of base-line and chemical-induced transcriptomic responses in HepaRG and RPTEC/TERT1 cells using TempO-Seq

Abstract: The utilisation of genome-wide transcriptomics has played a pivotal role in advancing the field of toxicology, allowing the mapping of transcriptional signatures to chemical exposures. These activities have uncovered several transcriptionally regulated pathways that can be utilised for assessing the perturbation impact of a chemical and also the identification of toxic mode of action. However, current transcriptomic platforms are not very amenable to high-throughput workflows due to, high cost, complexities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…Fluphenazine has not been established as a ligand for the AhR, its structure—a halogenated aromatic ring system—closely matches the motif involved in binding to this receptor (Donohoe et al, 2008 ). In a recent study we have demonstrated that isoniazid induced CYP1A1 in HepaRG cells, which is a potential indicator of AhR activation (Limonciel et al, 2018 ). Only Sulindac from the 160 was ranked as active using the CAC selection criteria, which may seem surprising given the frequency of oxidative injury in liver toxicities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Fluphenazine has not been established as a ligand for the AhR, its structure—a halogenated aromatic ring system—closely matches the motif involved in binding to this receptor (Donohoe et al, 2008 ). In a recent study we have demonstrated that isoniazid induced CYP1A1 in HepaRG cells, which is a potential indicator of AhR activation (Limonciel et al, 2018 ). Only Sulindac from the 160 was ranked as active using the CAC selection criteria, which may seem surprising given the frequency of oxidative injury in liver toxicities.…”
Section: Discussionmentioning
confidence: 98%
“…Potassium bromate is an oxidizing agent causing ROS injury and oxidative stress-induced DNA damage (Ballmaier and Epe, 1995 ; Limonciel et al, 2012 ). In a recent study we showed that potassium bromate activated the Nrf2 and p53 response without activation of the ATF4 response (Limonciel et al, 2018 ). Phorone can similarly activate Nrf2 due to glutathione depletion (Younes et al, 1986 ; Iannone et al, 1990 ; Oguro et al, 1996 ).…”
Section: Introductionmentioning
confidence: 97%
“…Transcriptomics was applied as a broad nontargeted biological screen of in vitro cellular perturbation following coumarin treatment, to complement the targeted assays (eg, Eurofins SafetyScreen44, and BioMap). Use of concentration-response modeling of transcriptomics data has been utilized to derive PoDs for chemical risk assessment ( Farmahin et al , 2017 ; Thomas et al , 2013 , 2019 ) and to identify potential MoAs for target organ toxicity ( Limonciel et al , 2018 ; Ramaiahgari et al , 2019 ). This study used 3 different cell lines (HepG2, MCF7, and 2D HepaRG) to extend biological coverage and address potential cellular variation in response to coumarin including any consequences of metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of newer platforms such as TempO-Seq targeted RNA sequencing, there has not been an evaluation of the performance of several normalization methods. Recent publications using the TempO-Seq platform used DESeq2 or CPM for normalization (Grimm et al, 2016;House et al, 2017;Yeakley et al, 2017;Batai et al, 2018;Bushel et al, 2018;Hanke et al, 2018;Limonciel et al, 2018;Chappell et al, 2019;Ramaiahgari et al, 2019;Simon et al, 2019). In this study, we compared seven normalization methods using simulated data from human HepaRG control cells to determine which methods maintained genes at seven assigned FC levels ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, by nature of the technology, it lacks 3 end bias. Recently, several studies utilized the TempO-Seq platform for whole transcriptome profiling, primarily for toxicogenomics (Grimm et al, 2016;House et al, 2017;Yeakley et al, 2017;Bushel et al, 2018;Limonciel et al, 2018;Chappell et al, 2019;Ramaiahgari et al, 2019;Simon et al, 2019), but also carcinogenomics (Batai et al, 2018;Hanke et al, 2018), and to profile formalin-fixed paraffin-embedded (FFPE) tissue (Trejo et al, 2019). However, there has not been a comprehensive comparison of normalization methods applied to TempO-Seq data.…”
Section: Introductionmentioning
confidence: 99%